Respuesta :

Answer:

12x² - 2x - 30

Step-by-step explanation:

When multiplying binomials, remember to follow the FOIL method:

FOIL =

First

Outside

Inside

Last

Follow FOIL: (3x - 5)(4x + 6)

(3x)(4x) = 12x²

(3x)(6) = 18x

(-5)(4x) = -20x

(-5)(6) = -30

Combine like terms, simplify:

12x² + 18x - 20x - 30

12x² + (18x - 20x) - 30

12x² - 2x - 30

12x² - 2x - 30 is your answer.

~

Answer:

12x²-2x-30=2(6x²-x-15)

Step-by-step explanation:

(3x-5)(4x+6)=12x²-20x+18x-30=

12x²-2x-30=2(6x²-x-15)

ACCESS MORE